2012
DOI: 10.1002/acr.21590
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disadvantage, individual‐level socioeconomic position, and self‐reported chronic arthritis: A cross‐sectional multilevel study

Abstract: Objective. To examine the association between individual-and neighborhood-level disadvantage and self-reported arthritis. Methods. We used data from a population-based cross-sectional study conducted in 2007 among 10,757 men and women ages 40 -65 years, selected from 200 neighborhoods in Brisbane, Queensland, Australia using a stratified 2-stage cluster design. Data were collected using a mail survey (68.5% response). Neighborhood disadvantage was measured using a census-based composite index, and individual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
5
32
2
1
Order By: Relevance
“…Similar associations between arthritis overall, and rheumatoid arthritis, and SES were observed Australia-wide in 2007–8 [10]. We have previously reported using multi-level analysis that a 42% increased likelihood of arthritis existed for those of greater social disadvantage compared to those who are more advantaged, even after accounting for disadvantage measured at the individual- and household-levels [5]. Furthermore, these differences were independent of advancing age and female sex; both factors that are associated with an increased prevalence of OA.…”
Section: Introductionsupporting
confidence: 64%
“…Similar associations between arthritis overall, and rheumatoid arthritis, and SES were observed Australia-wide in 2007–8 [10]. We have previously reported using multi-level analysis that a 42% increased likelihood of arthritis existed for those of greater social disadvantage compared to those who are more advantaged, even after accounting for disadvantage measured at the individual- and household-levels [5]. Furthermore, these differences were independent of advancing age and female sex; both factors that are associated with an increased prevalence of OA.…”
Section: Introductionsupporting
confidence: 64%
“…In contrast to our findings, some studies have shown that the prevalence of chronic pain was higher in individuals that live in urban areas characterized by poor education, social networks, and income [16,20], but high SGIx [15]. On the other hand, a multilevel model study developed in Australia showed a higher prevalence of arthritis in communities with a high SGIx [16].…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, a multilevel model study developed in Australia showed a higher prevalence of arthritis in communities with a high SGIx [16]. Explanations for this include the case definitions based on self-reports, the fact that these studies were conducted in developed countries where socioeconomic inequalities are not as marked as those in developing countries, and the use of different social indicators in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that income and education are likely to be closely linked, but with one influencing the other via distinct aetiological pathways. 47,48 Educational attainment for example, may influence the acquisition of knowledge about appropriate health practices, which may facilitate or constrain one's ability to maintain good physical function; whereas household income is likely to reflect the availability of resources to access health facilities and services. 47,49 This investigation is the first-known study to examine cross-level interactions epidemiological studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…47,48 Educational attainment for example, may influence the acquisition of knowledge about appropriate health practices, which may facilitate or constrain one's ability to maintain good physical function; whereas household income is likely to reflect the availability of resources to access health facilities and services. 47,49 This investigation is the first-known study to examine cross-level interactions epidemiological studies. [50][51][52] For instance, people with disability who live outside major cities may fare worse than their counterparts living in major cities, or people with no disability who live outside major cities.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%